Establishment and characterization of metastatic gastric cancer cell lines from murine gastric adenocarcinoma lacking Smad4, p53, and E‐cadherin. Issue 11 (12th October 2014) - Park, Jun Won; Park, Dong Min; Choi, Beom K.; Kwon, Byoung S.; Seong, Je Kyung; Green, Jeffrey E.; Kim, Dae‐Yong; Kim, Hark Kyun
<x xml:space="preserve">Abstract</x> There is a strong need for murine gastric cancer cell line models recapitulating human gastric cancers. Here, we describe two murine gastric cancer cell lines designated as NCC‐S1 and NCC‐S3. They were generated from gastric adenocarcinomas that formed in a Villin‐cre, Smad4F/F, Trp53F/F, Cdh1F/wt mouse and a Pdx1‐cre, Trp53F/F, Cdh1F/F mouse, respectively. Molecular profiles of both cell lines were very similar to human gastric cancer. NCC‐S1M and NCC‐S3M subpopulation clones were isolated from pulmonary metastasis of heterotopic allografts of NCC‐S1 and NCC‐S3 cells, respectively. NCC‐S1M and NCC‐S3M showed enhanced in vivo growth rates and metastatic potentials and exhibited epithelial‐to‐mesenchymal transition features. NCC‐S1M cells developed orthotopic and heterotopic tumors in immunocompetent mice in predictable manner, and were useful for testing the efficacy of an immunotherapeutic agent, anti‐4‐1BB antibody. NCC‐S1M and NCC‐S3M cells demonstrated Wnt/β‐catenin pathway activation, and knockdown of Ctnnb1 reversed the metastatic phenotype of NCC‐S1M. These results underscore the role of Wnt/β‐catenin pathway in metastatic phenotype of gastric cancer. Taken together, our novel metastatic gastric cancer cell lines are useful resources for drug development and metastasis research. © 2014 Wiley Periodicals, Inc.